1994
DOI: 10.1159/000100330
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic Radiosurgery for the Treatment of Low-Flow Carotid-Cavernous Fistulae: Results in a Series of 25 Cases

Abstract: 25 patients with low-flow carotid-cavernous fistula (CCF) underwent radiosurgery between 1977 and 1992. 22 had spontaneous low flow fistulae and 3 traumatic high flow fistulae which had been previously treated with internal carotid trapping. The mean preoperative symptomatic period was 12.2 months (4–24 months). Fistulae were classified according to Barrow''s classification. Type T was added for traumatic, high-flow fistulae with flow reduction after internal carotid trapping. 11 cases were of type B, 4 of typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(26 citation statements)
references
References 12 publications
0
24
0
1
Order By: Relevance
“…Barcia-Salorio et al 3 reported complete or near-complete reversal of the neuroophthalmological symptoms associated with indirect CCFs in 91.6% of patients with spontaneous, low-flow lesions treated with radiosurgery. However, in patients presenting with previously treated direct CCFs, radiosurgery was effective in only 2 of 5 patients.…”
Section: Radiosurgical Interventionmentioning
confidence: 99%
See 1 more Smart Citation
“…Barcia-Salorio et al 3 reported complete or near-complete reversal of the neuroophthalmological symptoms associated with indirect CCFs in 91.6% of patients with spontaneous, low-flow lesions treated with radiosurgery. However, in patients presenting with previously treated direct CCFs, radiosurgery was effective in only 2 of 5 patients.…”
Section: Radiosurgical Interventionmentioning
confidence: 99%
“…Other small series of patients with indirect CCFs have shown long-term obliteration of the fistula after treatment with radiosurgery in 75%-100% of patients. 3,17,28,53,64 Radiosurgery should not be used in emergency cases, as there is a latency of several months to years before complete obliteration of the CCF is accomplished. …”
Section: Radiosurgical Interventionmentioning
confidence: 99%
“…Several series have reported success rates in 59% to 95% of patients using these techniques. Recalcitrant cases have been controlled with carotid ligation and radiosurgery [24,26].…”
Section: Course and Treatmentmentioning
confidence: 99%
“…Barcia-Salorio et al [26] reported their experience with stereotactic radiosurgery in 25 patients with low-flow fistulae; 11 cases were type B, four were type C, seven were type D and three were previously treated direct CCFs. Patients had 30 to 40 cGy delivered to the fistulae and 91% were found to be closed within 7 months.…”
Section: Diagnosis and Therapymentioning
confidence: 99%
“…It has been used to treat indirect CCFs. In selected small series of patients with indirect CCFs, the treatment results have been good, with cure rates of 75-100% [49,50]. There are no reports in the literature of cure for direct CCFs.…”
Section: Radiosurgerymentioning
confidence: 96%